Germany's next top manager: Does personality explain the gender career gap? - Simon Fietze; Elke Holst; Verena Tobsch (Management Revue, 2011)
Many studies have focused on the influence of human capital and other objective factors on career achievement. In our study, we go a step further by also looking at the impact of self-reported personality traits on differences in career chances. For the first time - to our knowledge - we compare managers and other white-collar employees in Germany's private sector and find evidence that personality traits do influence the promotion probability even though their impact is rather small. With regard to differences in the promotion probability between women and men, bivariate results based on data from the German Socio-Economic Panel (SOEP) in 2007 show significant differences in personality traits. But multivariate estimations clearly indicate that these differences cannot account for gender differences in the promotion probability to a large extent. The decomposition (according to Fairlie, 2003) of the career gap between women and men shows that only 8.6 percent of the inequality of career chances can be explained by differences in personality. Nevertheless, personality traits might indeed play a role, albeit more indirectly: Some of the stronger career effects, such as long working hours, and labour market segregation, may also reflect differences in personality traits.
Keywords: D23; J16; J79; M12; 650; personality; gender; career; leadership